2013
DOI: 10.1159/000356577
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of the Na+/H+Exchanger Regulatory Factor (NHERF) Family of Adaptor Proteins with the Raft- and the Non-Raft Brush Border Membrane Fractions of NHE3

Abstract: Background/Aims: Trafficking, brush border membrane (BBM) retention, and signal-specific regulation of the Na+/H+ exchanger NHE3 is regulated by the Na+/H+ Exchanger Regulatory Factor (NHERF) family of PDZ-adaptor proteins, which enable the formation of multiprotein complexes. It is unclear, however, what determines signal specificity of these NHERFs. Thus, we studied the association of NHE3, NHERF1 (EBP50), NHERF2 (E3KARP), and NHERF3 (PDZK1) with lipid rafts in mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
4
22
0
Order By: Relevance
“…NHERF2 mRNA was not investigated because its absence does not result in a decrease in acid-activated NHE3 activity in murine colon [ 8 ], and because of its low colonic expression [ 19 ]. In addition, the cross-reactivity of the NHERF2 antibody with the much more strongly expressed NHERF1 [ 35 ] would make interpretation of the results difficult. We also studied three inflammatory mouse models, each of which had an immunologically mediated intestinal inflammation, but with different segment predilection, acuity, and severity of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…NHERF2 mRNA was not investigated because its absence does not result in a decrease in acid-activated NHE3 activity in murine colon [ 8 ], and because of its low colonic expression [ 19 ]. In addition, the cross-reactivity of the NHERF2 antibody with the much more strongly expressed NHERF1 [ 35 ] would make interpretation of the results difficult. We also studied three inflammatory mouse models, each of which had an immunologically mediated intestinal inflammation, but with different segment predilection, acuity, and severity of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NHE3 activity and membrane expression were reduced, although mRNA levels were not affected (21). One study found NHERF2 Ϫ/Ϫ mice to have lower ileal NHE3 activity due to impaired trafficking or retention of NHE3 in the apical membrane (99), which is possibly related to NHERF2 association with lipid-raft NHE3 (136). In fact, lysophosphatidic acid (LPA, released in inflammatory settings to repair wounded tissue) stimulates NHE3 activity and expression through NHERF2-dependent mechanisms in ileum (99) and kidney brush border (27, 84).…”
Section: Healthy Intestinal Tract Epitheliummentioning
confidence: 99%
“…They perform crucial roles in the establishment of cell polarity [9,10] and act as platforms mediating signal transduction and protein trafficking [11,12,13]. A number of raft-associated proteins have been identified, including tyrosine kinase cascades, G protein-coupled receptors, Src family kinases, and cytoskeletal and intermediate filament proteins [14].…”
Section: Introductionmentioning
confidence: 99%